Pengaruh ROA, ROE, NPM, dan EPS terhadap Harga Saham Perusahaan Sub Sektor Asuransi yang Terdaftar di BEI Tahun 2017-2020 - Dedi Suselo; Tanty Dwi Francisca (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the effect of ROA, ROE, NPM, and EPS on stock prices in the Indonesian insurance business sub-sector traded on the Indonesia Stock Exchange (IDX) between 2017 and 2020. The Indonesia Stock Exchange is the subject of this investigation. It is determined that return on assets (ROA), profit margin (NPM), and EPS are independent variables for this study, but stock prices are considered as the dependent variable. Return on Assets, Return on Equity, Earning Per Share, and Net Profit Margin are acronyms that can be used interchangeably. each. each. Quantitative techniques were used, and panel data served as the basis for further research to be carried out. The information used comes from secondary sources, and is collected from 10 separate businesses using purposive sampling according to a set of criteria. After that, tests were carried out on this dataset using the previously mentioned Eviews 10. Research efforts that rely heavily on the t-test as the main analytical technique have come to the conclusion that return on assets (ROA), return on equity (ROE), and net profit margin (NPM) have a value of zero, tone, nil, and tone have a relationship with movement share price in any way, shape, or form. Neither the number of shares outstanding nor earnings per share have an effect on share value (EPS). According to the F test, the company's return on assets (ROA), net profit margin (NPM), and earnings per share (EPS) all have an impact on its stock price. Keywords : Return On Assets; Return On Equity; Net Profit Margin; Earnings Per Share; Stock price.